subject
Mathematics, 05.05.2021 01:00 Nobleufia

The work of a student to solve the equation 3(2x − 4) = 8 + 2x + 6 is shown below: Step 1: 3(2x − 4) = 8 + 2x + 6 Step 2: 5x − 7 = 14 + 2x Step 3: 5x − 2x = 14 + 7 Step 4: 3x = 21 Step 5: x = 7 In which step did the student first make an error and what is the correct step? (5 points) Group of answer choices Step 3; 5x + 2x = 14 + 7 Step 3; 5x − 2x = 14 − 7 Step 2; 6x − 12 = 14 + 2x Step 2; 6x − 7 = 2(6 + x + 4)

ansver
Answers: 1

Another question on Mathematics

question
Mathematics, 21.06.2019 18:30
Evaluate cos2θ for cosθ = square root of 3/2
Answers: 1
question
Mathematics, 21.06.2019 19:00
Solve 3x-18=2y and 5x-6y=14 by elimination or substitution . show all !
Answers: 1
question
Mathematics, 21.06.2019 20:30
Write the summation to estimate the area under the curve y = 1 + x2 from x = -1 to x = 2 using 3 rectangles and right endpoints
Answers: 1
question
Mathematics, 21.06.2019 21:50
What is the next step in the given proof? choose the most logical approach. a. statement: m 1 + m 2 + 2(m 3) = 180° reason: angle addition b. statement: m 1 + m 3 = m 2 + m 3 reason: transitive property of equality c. statement: m 1 = m 2 reason: subtraction property of equality d. statement: m 1 + m 2 = m 2 + m 3 reason: substitution property of equality e. statement: 2(m 1) = m 2 + m 3 reason: substitution property of equality
Answers: 3
You know the right answer?
The work of a student to solve the equation 3(2x − 4) = 8 + 2x + 6 is shown below: Step 1: 3(2x − 4)...
Questions
question
English, 18.06.2021 14:00
question
Mathematics, 18.06.2021 14:00
question
English, 18.06.2021 14:00
question
Mathematics, 18.06.2021 14:00
question
Mathematics, 18.06.2021 14:00
question
World Languages, 18.06.2021 14:00
Questions on the website: 13722363